Ubiquitylation of Rad51d Mediated by E3 Ligase Rnf138 Promotes the Homologous Recombination Repair Pathway. - Deqiang Han; Junbo Liang; Yalan Lu; Longchang Xu; Shiying Miao; Lin-Yu Lu; Wei Song; Linfang Wang (PLoS ONE)
Ubiquitylation has an important role as a signal transducer that regulates protein function, subcellular localization, or stability during the DNA damage response. In this study, we show that Ring domain E3 ubiquitin ligases RNF138 is recruited to DNA damage site quickly. And the recruitment is mediated through its Zinc finger domains. We further confirm that RNF138 is phosphorylated by ATM at Ser124. However, the phosphorylation was dispensable for recruitment to the DNA damage site. Our findings also indicate that RAD51 assembly at DSB sites following irradiation is dramatically affected in RNF138-deficient cells. Hence, RNF138 is likely involved in regulating homologous recombination repair pathway. Consistently, efficiency of homologous recombination decreased observably in RNF138-depleted cells. In addition, RNF138-deficient cell is hypersensitive to DNA damage insults, such as IR and MMS. And the comet assay confirmed that RNF138 directly participated in DNA damage repair. Moreover, we find that RAD51D directly interacted with RNF138. And the recruitment of RAD51D to DNA damage site is delayed and unstable in RNF138-depleted cells. Taken together, these results suggest that RNF138 promotes the homologous recombination repair pathway.